PEMBERDAYAAN PEREMPUAN MELALUI GERAKAN PEREMPUAN ISLAM AISYIYAH PROVINSI LAMPUNG - Hidayati, Dewi Ayu (JURNAL SOSIOLOGI, 2013)
This study observes the phenomenon of existence of women movement Aisyiyah Lampung Province in empowering women. The discussionÂ  emphasizes on the implementation of Aisyiahâs programs in empowering women as well as the suporting and hampering factors of the empowering process. This research is descriptive which empolys qualitative approach in data analysis. Meanwhile the technique of collecting data are interview, observation and documentation. The result of the reseach shows that Aisyiyah Lampung province has successfully performed some efforts of empowering women in many sectors of life such as education, economy, social welfare, religion and environment. The supporting factors of this success are the existence of Memorandum of Understanding (MoU) between Aisyiah Lampung province and Aisyiyah head office Jakarta and also MoU between Aisyiyah Lampung and govermentâsÂ  institutions in Lampung. Other keys of success are the enthusiasm and full support of Aisyiyah members to the implementation of the programs. Whereas the hampering factors are the busy activities of its organizers, the minimum budgetÂ  for the realization of activities, and the low-interconecting regions in Lampung.Â  However in order to be more active in taking role of society empowerment, Aisyiyah insitution needs to improve the human resource quality of its members and organizers by conducting leadership training, developing its network, as well as applying good organization management so as to be the agent of social change.